Identification of novel biomarkers, shared molecular signatures and immune cell infiltration in heart and kidney failure by transcriptomics - Long, Qingqing; Zhang, Xinlong; Ren, Fangyuan; Wu, Xinyu; Wang, Ze-Mu (Frontiers in Immunology, 2024)
Heart failure (HF) and kidney failure (KF) are closely related conditions that often coexist, posing a complex clinical challenge. Understanding the shared mechanisms between these two conditions is crucial for developing effective therapies. This study aims to unveil the molecular signatures and identify novel biomarkers for both HF and KF. Through transcriptomic analysis, 2869 shared differentially expressed genes (DEGs) were identified in patients with HF and KF compared to healthy controls. Functional enrichment analysis of these genes indicated that the common mechanisms underlying HF and KF are associated with cellular homeostasis, cell communication, cellular replication, inflammation, and extracellular matrix (ECM) production. Notably, the P13K-Akt signaling pathway was primally enriched. A proteinprotein interaction (PPI) network was constructed to characterize the hub genes, revealing two key protein clusters related to the cell cycle and inflammation. Machine learning algorithms, including Random Forest (RF), Support Vector Machine-Recursive Feature Elimination (SVM-RFE), and Least Absolute Shrinkage and Selection Operator (LASSO), identified CDK2 and CCND1 as signature genes for both HF and KF. These genes were further analyzed using Gene Set Variation Analysis (GSVA) and Gene Set Enrichment Analysis (GSEA). Their diagnostic value was validated in both training and validation sets. Additionally, a CDK2 activator was selected to dock with CCND1, and a CCND1 inhibitor was selected to dock with CDK2 to evaluate potential drug candidates, although further cytotoxicity assessments are needed. Immune cell infiltration analysis in HF and KF patients versus healthy controls, along with correlation analyses between various immune cell types and signature genes, revealed that CDK2 and CCND1 are correlated with immune response.Conclusively, this study identifies CDK2 and CCND1 as novel biomarkers that link cell cycle regulation and inflammation in heart and kidney failure. These findings offer new insights into the molecular mechanisms of HF and KF and present potential targets for diagnosis and therapy.